2009
DOI: 10.1002/lt.21721
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for developing de novo autoimmune hepatitis associated with anti-glutathione S-transferase T1 antibodies after liver transplantation

Abstract: De novo autoimmune hepatitis (de novo AIH) is a rare form of graft dysfunction that develops after liver transplantation (LT) in patients transplanted for conditions other than autoimmune disorders. Although characterized by biochemical, serological, and histological features of AIH, de novo AIH is sometimes associated with atypical serum autoantibodies, many of which are directed against glutathione S-transferase T1 (anti-GSTT1). GSTT1 donor/recipient genotype mismatch has been suggested as a necessary condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 31 publications
1
28
2
Order By: Relevance
“…Numerous studies have described classical biochemical, immunological, and histological features of AIH developing in patients transplanted for other diseases [35,43,[97][98][99][100][101][102][103][104][105][106]. A higher frequency has been reported in children (5-10%) compared with adults (1-2%), possibly related to immunosuppressive drugs interfering with normal T cell maturation in the immature immune system.…”
Section: De Novo Autoimmune Hepatitismentioning
confidence: 93%
See 1 more Smart Citation
“…Numerous studies have described classical biochemical, immunological, and histological features of AIH developing in patients transplanted for other diseases [35,43,[97][98][99][100][101][102][103][104][105][106]. A higher frequency has been reported in children (5-10%) compared with adults (1-2%), possibly related to immunosuppressive drugs interfering with normal T cell maturation in the immature immune system.…”
Section: De Novo Autoimmune Hepatitismentioning
confidence: 93%
“…Many studies have identified overlapping areas between de novo AIH and rejection -these include autoantibodies being present, sometimes transiently, in otherwise typical episodes of rejection (acute and chronic) [35,102,108,109], previous acute rejection episodes being a risk factor for the development of de novo AIH [43,99,104] and, as discussed earlier, features of de novo AIH arising in the setting of under-immunosuppression [73] or when the recipient's immune system is stimulated by anti-viral treatment with interferon [68][69][70][71]. Perhaps the most convincing evidence for an alloimmune response has come from two Spanish groups, who both found that the de novo AIH occurred exclusively in glutathione-S-transferase T1 (GSTT1) negative recipients of a GSTT1-positive donor liver and was associated with the development of donor-specific anti-GSTT1 antibodies [100,101,103,105]. As the GSTT1 enzyme is expressed by hepatocytes in GSTT1-positive individuals, the development of de novo AIH in the setting of a donor/recipient mismatch for GSST1 may thus represent a form of late rejection, in which immune-mediated injury is mainly directed towards hepatocytes [17].…”
Section: De Novo Autoimmune Hepatitismentioning
confidence: 97%
“…Several features suggest an overlap between de novo AIH and cellular rejection, this includes the findings that previous episodes of AR are a risk factor for de novo AIH, the transient presence of autoantibodies during typical episodes of AR and features of de novo AIH arising in situations of under-immunosuppression [85,151,[177][178][179][180][181][182]. Furthermore, two groups have reported the exclusive presentation of de novo AIH in glutathione-S-transferase T1 (GSTT1) negative recipients of a GSTT1-positive donor, who develop donor-specific anti-GSTT1 antibodies [176,[183][184][185]. This may be a form of late rejection directed against hepatocytes since the GSTT1 enzyme is expressed by hepatocytes [77].…”
Section: De Novo Aihmentioning
confidence: 97%
“…In support of this suggestion, autoantibodies have been described transiently in association with episodes of acute and chronic rejection [187][188][189][190], previous episodes of acute rejection have been reported as having predictive value for the subsequent development of de novo AIH [183,184,186] and de novo AIH may arise in the setting of suboptimal immunosuppression [191] or as a consequence of non-specific stimulation of the immune system by interferon therapy for HCV infection [192][193][194]. Perhaps, the most convincing evidence for an alloimmune response is the observation that the development of de novo AIH was closely associated with antibodies to glutathione-Stransferase T1 (GSTT1) developing in a GSST1-negative recipient of a GSTT1-positive graft [195][196][197][198]. As the GSST1 enzyme is expressed by hepatocytes in the liver allograft, this could represent a form of alloimmune injury (i.e., rejection) directed against hepatocytes.…”
Section: De Novo Aihmentioning
confidence: 99%